Answer:
1.075
Step-by-step explanation:
cuz I said so
Answer:
11 - 3i = 44 (move 11 to the right side and add minus)
-3i = 44-11
-3i = 33 (dive it by -3)
i = -11
Answer:
1. 3 2. 16
Step-by-step explanation:
3x+2/y, x = 3 and y = 6
3(3)/6
Factor the number
3*3*2/3*2
Cancel the common factor (3)
3*2/2
Cancel the common factor (2)
3/1
Simplify
=3
(4a)^3/(b-2), a = 2, b = 4
(4(2)^3/(4-2)
Subtract the numbers:
2^3 * 4/2
Apply exponent rule (a^b*a^c=a^b+c)
= 2^3+1
Add the numbers:
2^4
Simplify:
=16
Answer:
34.3 in, 36.3 in
Step-by-step explanation:
From the question given above, the following data were obtained:
Hypothenus = 50 in
1st leg (L₁) = L
2nd leg (L₂) = 2 + L
Thus, we can obtain the value of L by using the pythagoras theory as follow:
Hypo² = L₁² + L₂²
50² = L² + (2 + L)²
2500 = L² + 4 + 4L + L²
2500 = 2L² + 4L + 4
Rearrange
2L² + 4L + 4 – 2500 = 0
2L² + 4L – 2496 = 0
Coefficient of L² (a) = 2
Coefficient of L (n) = 4
Constant (c) = –2496
L = –b ± √(b² – 4ac) / 2a
L = –4 ± √(4² – 4 × 2 × –2496) / 2 × 2
L = –4 ± √(16 + 19968) / 4
L = –4 ± √(19984) / 4
L = –4 ± 141.36 / 4
L = –4 + 141.36 / 4 or –4 – 141.36 / 4
L = 137.36/ 4 or –145.36 / 4
L = 34.3 or –36.3
Since measurement can not be negative, the value of L is 34.3 in
Finally, we shall determine the lengths of the legs of the right triangle. This is illustrated below:
1st leg (L₁) = L
L = 34.4
1st leg (L₁) = 34.3 in
2nd leg (L₂) = 2 + L
L = 34.4
2nd leg (L₂) = 2 + 34.3
2nd leg (L₂) = 36.3 in
Therefore, the lengths of the legs of the right triangle are 34.3 in, 36.3 in
Donuts because I really like them